Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.21203/rs.3.rs-16570/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Overexpression of TGFβ1 in murine mesenchymal stem cells improves lung inflammation by impacting the Th17/Treg balance in LPS-induced ARDS mice

Abstract: Background: T helper 17 cells (Th17) /regulatory T cells (Treg), as subtypes of CD4+ T cells, play an important role in the inflammatory response of acute respiratory distress syndrome (ARDS). However, there is still a lack of effective methods to regulate the differentiation balance of Th17/Treg. It was proven that mesenchymal stem cells (MSCs) could regulate the differentiation of CD4+ T cells, but the mechanism is still unclear. TGFβ1, a paracrine cytokine of MSCs, could also regulate the differentiation of… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 12 publications
(23 reference statements)
1
4
0
Order By: Relevance
“…The immunomodulatory effects of MSCs in the respiratory system involve T-cell differentiation. 32 In this study, the therapeutic effects of MSCs were found to be mediated by reduced infiltration of Ly6C + CD8 + T cells, in line with the lower IFNγ level in the LPS/ MSC group, since excessive IFNγ synthesized by large numbers of CD8 + T cells can aggravate tissue injury. 50 Moreover, enhanced macrophage phagocytosis in MSC-treated mice contributed to repair of injured tissue, which is consistent with a prior report.…”
Section: Discussionsupporting
confidence: 58%
See 4 more Smart Citations
“…The immunomodulatory effects of MSCs in the respiratory system involve T-cell differentiation. 32 In this study, the therapeutic effects of MSCs were found to be mediated by reduced infiltration of Ly6C + CD8 + T cells, in line with the lower IFNγ level in the LPS/ MSC group, since excessive IFNγ synthesized by large numbers of CD8 + T cells can aggravate tissue injury. 50 Moreover, enhanced macrophage phagocytosis in MSC-treated mice contributed to repair of injured tissue, which is consistent with a prior report.…”
Section: Discussionsupporting
confidence: 58%
“…The anti-inflammatory properties of MSCs have been described. 32,47 In this study, MSCs ameliorated inflammatory response in BALF, as indicated by decreased levels of IFNγ, TNFα, IL-1α, IL-1β and IL-6. Our results are consistent with the previous studies on the anti-inflammatory effects of MSCs in ALI.…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations